Factors Affecting Consumers' Online Buying Intention: A Comparative Study of Azerbaijan and Türkiye - Nihad Gurbanli; Ayşegül Karataş (İşletme Bilimi Dergisi)
Factors affecting online purchase intention may vary depending on culture and the development level of e-commerce across nations. This research focuses on different levels of e-commerce development and controls the cultural differences using samples from Türkiye and Azerbaijan to find out any differences in antecedents of online buying behavior. The study model is based on the Theory of Planned Behavior (Ajzen, 1991), using self-efficacy, subjective norms, and four dimensions of perceived risk as independent variables, while also examining the mediating role of trust in online purchase intention. Data were collected from a total of 406 consumers in Azerbaijan and Türkiye through an online survey using the convenience sampling method. Data was analysed with Structural Equation Modeling (SEM). The findings reveal that subjective norms and self-efficacy positively and significantly influence purchase intention in both countries. However, trust served as a partial mediator of online purchase intention in Türkiye, while in Azerbaijan, trust did not mediate the relationship. Additionally, in Azerbaijan, perceived risk influenced trust, whereas in Türkiye, this effect was not observed. The lack of repeated transaction experiences in Azerbaijan appears to be the primary reason for these differences.